Evaluating the use of luteal color Doppler ultrasonography and pregnancy-associated glycoproteins to diagnose pregnancy and predict pregnancy loss in Bos taurus beef replacement heifers. (12th October 2022) - Holton, Matthew P; de Melo, Gabriela D; Dias, Nicholas W; Pancini, Stefania; Lamb, Graham C; Pohler, Ky G; Mercadante, Vitor R G; Harvey, Kelsey M; Fontes, Pedro L P
Abstract: The objective of this study was to evaluate the use of corpus luteum (CL ) color Doppler (CD ) ultrasonography and pregnancy-associated glycoproteins (PAG ) for early pregnancy diagnosis and examine their ability to predict late embryonic/early fetal mortality (LEM ) in Bos taurus beef replacement heifers. Beef heifers ( n = 178) were exposed to a 7-d CO-Synch + CIDR protocol followed by fixed-time artificial insemination (day 0). On days 20 and 22, B-mode and CD ultrasonography were performed to evaluate CL morphometries and blood perfusion, respectively. Heifers were considered nonpregnant when CL area was <2 cm 2 or estimated luteal blood perfusion was ≤30% of the total luteal area. Blood samples were collected on days 25 and 29 to estimate circulating concentrations of PAG. Conventional ultrasonography on days 29 and 94 was utilized to determine pregnancy status and considered the gold standard method for pregnancy diagnosis. Pregnant heifers had greater ( P < 0.01) CL diameter, area, volume, and blood perfusion when compared with nonpregnant heifers on days 20 and 22. Accuracy of CD on days 20 and 22, and PAG on days 25 and 29 were 91%, 94%, 96%, and 98%, respectively. No false-negative results were observed for CD on both days 20 and 22 (negative predicted value = 100%) and false-positive results represented 8% and 6% of the diagnoses. Heifers that experienced LEM between days 29 and 94 of gestation had decreased luteal ( P = 0.02) volume on day 20 and tended ( P = 0.07) to have decreased concentrations of PAG on day 29 compared with heifers that maintained pregnancy. However, both CD and PAG failed to predict embryonic mortality. In conclusion, CD successfully detected most nonpregnant replacement heifers as early as day 20 of gestation, while resulting in no false negative diagnoses. Both CD and PAG failed to predict LEM in the present study. Abstract : Luteal color Doppler ultrasonography recognized most nonpregnant Bos taurus beef replacement heifers on days 20 and 22 of gestation and represent an alternative for early pregnancy detection. Plasma concentrations of pregnancy-associated glycoproteins and color Doppler ultrasonography failed to predict late embryonic mortality in heifers. Lay Summary: Identifying nonpregnant females early after breeding allows cattle producers to rapidly rebreed females that failed to conceive after their first artificial insemination and consequently increases reproductive efficiency. Additionally, embryonic and fetal mortality during early gestation are the main drivers of pregnancy failure and represents a significant economic burden to both the beef and dairy industries. This study evaluated the use of color Doppler (CD ) ultrasonography of specific ovarian structures and blood concentrations of pregnancy-associated glycoproteins (PAG ) as potential methods to diagnose pregnancy earlier than industry-standard techniques. Moreover, the present study investigated the use of CD and blood PAG as predictor of pregnancy loss. Data generated here indicates that CD and blood PAG can accurately detect pregnancy as early as 20 and 25 d after insemination, respectively. In the present study, heifers that experienced pregnancy loss between days 29 and 94 of gestation tended to have decreased plasma concentrations of PAG during early pregnancy. Heifers experiencing pregnancy loss between days 29 and 94 of gestation were also more likely to have a luteal cavity on day 20 of gestation and had decreased luteal volume on the same day. However, results reported herein indicate that both CD and blood concentrations of PAG failed to predict pregnancy loss in replacement heifers.